2011
DOI: 10.1007/s10494-011-9356-x
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of Dispersion from Line Sources in a Turbulent Channel Flow

Abstract: Large-eddy simulations of the dispersion from scalar line sources at various locations within a fully developed turbulent channel flow at Re = uh/ν = 10400 are presented. Both mean and fluctuating scalar quantities are compared with those from the single available set of experimental data (Lavertu and Mydlarski, 2005) and differences are highlighted and discussed. The results are also discussed in the context of scalar dispersion in other kinds of turbulent flows, e.g. homogeneous shear-flow. Initial computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
(86 reference statements)
2
17
2
Order By: Relevance
“…More recently, Boppana et al. ( 2012 ) studied the relatively simpler case of dispersion from a line source in channel flow at a finite Reynolds number of 10800 and still underlines the difficulty implied in investigating scalar dispersion from small sources by means of LES, and the need of thorough validations.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Boppana et al. ( 2012 ) studied the relatively simpler case of dispersion from a line source in channel flow at a finite Reynolds number of 10800 and still underlines the difficulty implied in investigating scalar dispersion from small sources by means of LES, and the need of thorough validations.…”
Section: Introductionmentioning
confidence: 99%
“…Stapountzis et al 1986;Lavertu and Mydlarski 2005;Lepore and Mydlarski 2011) and numerical (e.g. Boppana et al 2012) PDFs of passive scalar obtained in turbulent channels. Notably, Venaille and Sommeria (2008) have shown that in confined turbulence the gamma distribution (Eq.…”
Section: Analytical Pdf Modelsmentioning
confidence: 99%
“…Boppana et al. 2012 ) PDFs of passive scalar obtained in turbulent channels. Notably, Venaille and Sommeria ( 2008 ) have shown that in confined turbulence the gamma distribution (Eq.…”
Section: Phenomenologically-based Approachesmentioning
confidence: 99%
“…LES, which parametrizes the smallest scales of turbulence, has been successful in simulating dispersion at close and moderate distances from the source (e.g. Boppana et al (2010Boppana et al ( , 2012; Matheou et al (2016); Ardeshiri et al (2020)). DNS, which resolves all details of the flow, is now becoming affordable for atmospheric studies (e.g.…”
Section: Introductionmentioning
confidence: 99%